STATISTICAL ANALYSIS OF IMITATION WORDS (ON THE EXAMPLE OF TWO VOLUME AND FIVE VOLUME EXPLANATORY DICTIONARIES OF THE UZBEK LANGUAGE) (Scientific journal of the Fergana State University, 2024)
In this article, general statistics of imitation words available in the “Annotated Dictionary of the Uzbek language” (volumes 2 and 5) are given and different approaches related to their meaning and interpretation are compared. Also, the places where words with similar meaning are indicated with a symbol as a reference to imitation words are highlighted